The Role of the Private Sector in Regional Economic Integration: a View from the Philippines - Josef T. Yap; Maureen Ane D. Rosellon (Philippine Institute for Development Studies (PIDS), 2010)
The private sector is the driver of growth in most ASEAN economies. It is therefore expected to play a significant role in the process of economic integration in ASEAN. In the Philippines, the private sector has dominated the economy, contributing about 95 percent of GDP, but it has not lived up to its potential. Unlike other economies in East Asia, the Philippines did not experience the anticipated private sector participation and economic transformation that accompany the openness model of development. The ASEAN Economic Community is an extension of this paradigm. Philippine-based firms are found to have low utilization of arrangements in the ASEAN free trade agreement and private sector investment as a percentage of GDP is observed to be relatively low and to have consistently declined since 2000. This paper seeks to explain the reasons for the Philippines' relatively weak private sector response to the opportunities provided by greater openness and deepening regional economic integration. The paper cites some factors which include structural supply-side constraints and institutional weaknesses. Some of these factors are extraneous to the private sector but some emanate from the behavior of the private sector. These factors are expected to mitigate the impact of policies related to establishment of the AEC. However, there are pockets of success as a result of the move toward the AEC such as the launch of the National Single Window.
Keywords: 330; Philippines; private sector; openness model; oligarchy; ASEAN Economic Community (AEC); Privatwirtschaft; Handelsliberalisierung; Philippinen; Markteintritt; Regionale Wirtschaftsintegration; ASEAN-Staaten